KUALITAS PERENCANAAN PEMBANGUNAN PERANGKAT DAERAH DI LINGKUNGAN PEMERINTAH PROVINSI LAMPUNG - Ridwan Saifuddin 1 (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
The development planning document substantially describes the problems and priorities of development in the regions as the basis for the preparation of development programs and activities. Undang-Undang No. 25 Tahun 2004 about the National Development Planning System mandates that development planning documents be prepared with a political, technocratic, participatory, top-down, and bottom-up approach. The substance of the document must also meet the criteria of holistic, thematic, integrative, and spatial. This study uses a qualitative descriptive method, with primary data obtained through in-depth interviews with respondents from planning elements in regional offices within the Lampung Provincial Government. The results showed that the process of preparing development planning documents carried out by regional officials was still predominantly done on a top-down basis, and substantially not all of them met the holistic, thematic, integrative, and spatial criteria. Regional offices have also not implemented the development planning process in a synergistic, inter-sectoral integrated manner and supported by adequate data and information analysis. Improving the quality of development planning in regional offices requires commitment from regional offices leaders, in addition to the need to strengthen a more participatory and evidence-based development planning system.